Characterization and Transferable Utility of Microsatellite Markers in the Wild and Cultivated Arachis Species - Huang, Li (PLoS One, 2016)
Microsatellite or simple sequence repeat (SSR) is one of the most widely distributed molecular markers that have been widely utilized to assess genetic diversity and genetic mapping for important traits in plants. However, the understanding of microsatellite characteristics in Arachis species and the currently available amount of high-quality SSR markers remain limited. In this study, we identified 16,435 genome survey sequences SSRs (GSS-SSRs) and 40,199 expressed sequence tag SSRs (EST-SSRs) in Arachis hypogaea and its wild relative species using the publicly available sequence data. The GSS-SSRs had a density of 159.9–239.8 SSRs/Mb for wild Arachis and 1,015.8 SSR/Mb for cultivated Arachis, whereas the EST-SSRs had the density of 173.5–384.4 SSR/Mb and 250.9 SSRs/Mb for wild and cultivated Arachis, respectively. The trinucleotide SSRs were predominant across Arachis species, except that the dinucleotide accounted for most in A. hypogaea GSSs. From Arachis GSS-SSR and EST-SSR sequences, we developed 2,589 novel SSR markers that showed a high polymorphism in six diverse A. hypogaea accessions. A genetic linkage map that contained 540 novel SSR loci and 105 anchor SSR loci was constructed by case of a recombinant inbred lines F(6) population. A subset of 82 randomly selected SSR markers were used to screen 39 wild and 22 cultivated Arachis accessions, which revealed a high transferability of the novel SSRs across Arachis species. Our results provided informative clues to investigate microsatellite patterns across A. hypogaea and its wild relative species and potentially facilitate the germplasm evaluation and gene mapping in Arachis species.